Child welfare characteristics in a sample of youth involved in commercial sex: An exploratory study. (August 2019) - Greeson, Johanna K.P.; Treglia, Daniel; Wolfe, Debra Schilling; Wasch, Sarah; Gelles, Richard J.
Abstract: Background: Homeless, runaway, and youth exiting foster care are vulnerable to sexual exploitation, but little research has parsed the societal, community, and individual factors that contribute to their risk. Objectives: (1) To estimate child welfare characteristics in a sample of homeless young people who engaged in commercial sex (CS); and (2) To compare young people who were sex trafficked (ST) to those who engaged in some other form of CS. Participants and setting: This study includes 98 homeless young people in Philadelphia, PA, Phoenix, AZ, and Washington, DC, who were interviewed for a larger study of ST and endorsed engagement in CS. Methods: We used a non-probability, purposive, maximum variation sampling procedure. Interviews were recorded and responses were simultaneously noted on a standardized interview form. Data were analyzed through means, frequencies, and bivariate tests of association. Results: Average age of the full sample of 98 homeless young people was 20.9 years; 48% were female and 50% were Black/African American. Forty-six percent of the full sample was sex trafficked. The full sample and the victims of ST differed significantly in three child welfare characteristics, with the ST group more likely to have been maltreated as children, more likely to have had family involvement with the child welfare system (CWS), and more likely to report higher rates of living someplace other than with their biological parents as children. Conclusions: ST victims differ from those who engaged in other forms of CS in histories of maltreatment, involvement with the CWS, and exposure to residential instability while growing up.